Make the year with cubes!

If a a and b b are integers such that a 3 + b 3 = 2015 a^3+b^3=2015 , then what is a + b a+b ?


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

13 solutions

Andy Hayes
Aug 28, 2015

The sum of cubes a 3 + b 3 a^3+b^3 can be factored as ( a + b ) ( a 2 a b + b 2 ) (a+b)(a^2-ab+b^2) . If there exist integer solutions for a a and b b , then ( a + b ) (a+b) and ( a 2 a b + b 2 ) (a^2-ab+b^2) must be factors of 2015 2015 .

Let m = a + b m=a+b and n = a 2 a b + b 2 n=a^2-ab+b^2 . Solving this system of equations for a a and b b yields a = 3 m ± 12 n 3 m 2 6 a=\frac{3m\pm\sqrt{12n-3m^2}}{6} and b = m a b=m-a .

The possible factor pairs for 2015 2015 are: 1 × 2015 1\times2015 , 5 × 403 5\times403 , 13 × 155 13\times155 , and 31 × 65 31\times65 .

Substituting these factor pairs of 2015 2015 into m m and n n yields only two possible integer solutions for a a and b b : a = 14 a=14 and b = 9 b=-9 , or a = 9 a=-9 and b = 14 b=14 . In either case, a + b = 5 a+b=\boxed{5} .

a=3m+-sqr12n-3m2/6=?

Soner Karaca - 5 years, 9 months ago

Log in to reply

Solve for b b in m = a + b m=a+b :

b = m a b=m-a

Substitute expression for b b into n = a 2 a b + b 2 n=a^2-ab+b^2 , then simplify:

n = a 2 a ( m a ) + ( m a ) 2 n=a^2-a(m-a)+(m-a)^2

n = a 2 m a + a 2 + m 2 2 m a + a 2 n=a^2-ma+a^2+m^2-2ma+a^2

n = 3 a 2 3 m a + m 2 n=3a^2-3ma+m^2

Get into standard quadratic form for a a :

3 a 2 3 m a + ( m 2 n ) = 0 3a^2-3ma+(m^2-n)=0

Use quadratic formula to solve for a a in terms of m m and n n , then simplify:

a = 3 m ± 9 m 2 4 ( 3 ) ( m 2 n ) 6 a=\frac{3m\pm\sqrt{9m^2-4(3)(m^2-n)}}{6}

a = 3 m ± 12 n 3 m 2 6 a=\frac{3m\pm\sqrt{12n-3m^2}}{6}

Andy Hayes - 5 years, 9 months ago

Log in to reply

Andy Hayes thenks

Soner Karaca - 5 years, 9 months ago

I'm only 13 and we havnt covered this in school. Starting 8th grade in 2 months. And I want to know more about how you solved a+b.

Yesica Merino - 5 years ago

Log in to reply

There's a couple things involved in the solution that you might not have learned yet. I'm going to list them here so you can check out some of the other wikis. Hopefully you'll find some interesting things to learn over the summer!

  • Factoring an integer : One of the important steps of this problem was finding the factors of 2015 2015 . You probably have some experience finding factors of a number, but you might not know all of the "tricks."

  • Multiplying polynomials : It's important to know how to multiply polynomials to better understand how to factor them. "Factoring" polynomials is the inverse of "multiplying" polynomials. This means that they are opposite processes.

  • Factoring polynomials : Factoring the polynomial a 3 b 3 a^3-b^3 was the key step in solving this problem. This involves a special factoring identity, the " sum of cubes " identity.

  • Quadratic Formula : Using the quadratic formula was another key step in solving this problem. You might have some experience in solving linear equations , like 2 x + 3 = 11 2x+3=11 . This problem involves solving a quadratic equation , which is what the quadratic formula is used for.

Andy Hayes - 5 years ago

I did the same! The last few lines seem unneeded though. You check for each value of m. m=a+b so you don't really need to state the two possibilities of a and b. whichever m works would be equal to a+b

Shay Pecker - 4 years, 12 months ago

If a + b = 5 a+b=5 . Possible Values of a and b are 1 and 4, 2 and 3. How is this possible?

Rajdeep Ghosh - 4 years, 9 months ago

Log in to reply

The problem doesn´t specify that a and b have to be positive integers.

Ricardo Moritz Cavalcanti - 10 months, 2 weeks ago

Could you specify in the question that the integers can be both positive or negative? I know it may be unnecessary but it would save the user time. Thanks

Gilbert Yang - 4 years, 4 months ago
Otto Bretscher
Sep 3, 2015

We make four observations:

  1. a + b > 0 a+b>0 ,

  2. a 3 + b 3 2 ( m o d 3 ) a^3+b^3\equiv2\pmod{3} , so that a + b 2 ( m o d 3 ) a+b\equiv2\pmod{3} ,

  3. 2015 = a 3 + b 3 1 4 ( a + b ) 3 2015=a^3+b^3\geq{\frac{1}{4}(a+b)^3} for a + b > 0 a+b>0 , so that a + b 20 a+b\leq{20} , and

  4. a 3 + b 3 = ( a + b ) ( a 2 a b + b 2 ) a^3+b^3=(a+b)(a^2-ab+b^2) , so that a + b a+b divides 2015 = 5 × 13 × 31. 2015=5\times13\times31.

This leaves the possibility a + b = 5 a+b=\boxed{5} only.

Does this solution work if you don't know whether or not there must exist an integer solution?

Andy Hayes - 5 years, 9 months ago

Log in to reply

I'm sneakily and lazily taking advantage of the way the problem is phrased. Once we know that a + b = 5 a+b=5 is the only candidate, it would be a routine computation to check for integer solutions, of course..

Otto Bretscher - 5 years, 9 months ago

Could you explain why the 3rd fact a³+b³≧ (a+b)³/4 for a+b>0 is established?

流布 宿 - 1 year, 5 months ago

I know this doesn't prove anything at all (unlike other better solutions), but I wanted to share how I solved this problem computationally with this little program in Ruby (even if you don't know Ruby it isn't hard to understand):

a = b = 0
for i in -28..28 #edit
    for j in -28..28
        a = i
        b = j
        result = a**3 + b**3
        puts a + b if result == 2015
    end
end

#outputs:
#=> 5
#=> 5

Again, I guess this doesn't have mathematical rigor, but I found the answer quickly.

@edit: Actually, we can show that a and b must be both in the range [-27, 27] since 27³ - 26³ = 2107 > 2015. If we try a's and b's bigger than 27, no matter the combination we can't get 2015 with a³ + b³ (because it will be bigger). This solution uses simple brute force, but given this constraint it executes pretty fast (therefore, we can see that this implementation efficiency deppends on the size of the equation's right side).

We can even extend it to any right side number with:

a = b = 0
right_number = 2015
limit = 1
limit += 1 while (limit**3 - (limit - 1)**3) < right_number
for i in -limit..limit
    for j in -limit..limit
        a = i
        b = j
        result = a**3 + b**3
        puts a + b if result == right_number
    end
end
Laurent Shorts
Apr 9, 2016

a 3 + b 3 = ( a + b ) ( a 2 a b + b 2 ) = 2015 a^3+b^3=(a+b)(a^2-ab+b^2)=2015

So a + b a+b must be a factor of 2015: 1, 5, 13, 31, 5·13, 5·31, 13·31, 5·13·31= 2015. We can rule out 2015 as a 3 + b 3 > a + b a^3+b^3>a+b here (see comment below).

Modulus 7: x , x 3 0 \forall x, x^3\equiv 0 , x 3 1 x^3\equiv 1 or x 3 1 x^3\equiv -1 . a 3 + b 3 = 2015 1 a 3 0 , ( b 3 1 b 3 , 5 , 6 ) a^3+b^3=2015\equiv -1 \Rightarrow a^3\equiv 0, (b^3\equiv -1\leftrightarrow b\equiv3,5,6) or the opposite. Then, a + b 3 , 5 , 6 a+b\equiv 3,5,6 and that leaves only a + b = a+b= 5, 13 or 31.

Modulus 3: x , x 3 x \forall x, x^3\equiv x . So a 3 + b 3 a + b 2015 2 a^3+b^3 \equiv a+b \equiv 2015 \equiv 2 . That leaves only a + b = 5 \boxed{a+b=5} .


If we want a a and b b (for example to prove a solution really exists!), we solve a 3 + ( 5 a ) 3 = 2015 15 a 2 75 a + 125 = 2015 a^3+(5-a)^3=2015 \Leftrightarrow 15a^2-75a+125=2015 15 ( a 14 ) ( a + 9 ) = 0 \Leftrightarrow 15(a-14)(a+9)=0 . And we find 14 and -9.


a 3 + b 3 > a + b a^3+b^3>a+b :

As 2015 is not a cube, a a and b b can't be 0. As 2014 and 2016 are not cubes, they can't be 1 either.

As a 3 + b 3 = 2015 > 0 a 3 > b 3 a > b a + b > 0 a^3+b^3=2015>0 \Rightarrow a^3>-b^3 \Leftrightarrow a>-b \Leftrightarrow a+b>0 , then at most one of them can be negative.

Suppose, WLOG, that a b a\geq b , so a a and a b a-b are positive. a 2 a b + b 2 = a ( a b ) + b 2 b 2 > 1 a^2-ab+b^2=a(a-b)+b^2\geq b^2 > 1 .

Therefore a 3 + b 3 = ( a + b ) ( a 2 a b + b 2 ) > a + b a^3+b^3=(a+b)(a^2-ab+b^2)>a+b .

Sorry for revisiting an old problem. I'm having problems in understanding this part under Modulus 7:

> Then, a+b mod 3,5,6 and that leaves only a+b = 5, 13 or 31.

Could you pls explain that part? Thanks!

Ramasamy Pullappan - 3 years, 2 months ago

Log in to reply

As a 3 + b 3 1 a^3+b^3\equiv-1 , one must be 0 \equiv 0 and the other 1 \equiv -1 . Suppose it is a 3 0 a^3\equiv 0 and b 3 1 b^3\equiv -1 , then a 0 a\equiv 0 and b b\equiv 3, 5 or 6. Then, a + b a + b\equiv 3, 5 or 6.

The only possibilities in 1, 5, 13, 31… which are \equiv 3, 5 or 6 modulus 7 are a + b = 5 a+b=5 , 13 or 31.

Laurent Shorts - 3 years, 2 months ago

2015 is the product of 5, 13 and 31. Since a and b are said to be integers, 5 could be one of the three answers, the other two being 13 and 31.

Finn C
Jan 27, 2017

I actually didn't realise it could be negative numbers so I thought 13 would be maximum. Then I realise it couldn't work - with a little help from my trusty calculator. Eventually, through trial and error I found the answer.

Same, used excel to make up the cubes, the sum couldn't be done unless negatives were included, calculated them real quick and did the rest of the sum. I know it's cheating but I still felt that I had to work out the mechanics of the solution as the cubing part was beyond my mental math ability. For now anyway....

Simon Inniss - 4 years, 4 months ago
Maninder Dhanauta
Aug 18, 2016

a 3 + b 3 = ( a + b ) ( a 2 a b + b 2 ) = ( a + b ) ( ( a + b ) 2 3 a b ) = 5 13 31 [ f a c t o r s o f 2015 ] . L e t ( a + b ) = F : . F ( F 2 3 a b ) = 5 13 31 . ( F 2 3 a b ) = 5 13 31 F 5 2 ( m o d 3 ) 13 1 ( m o d 3 ) F 2 5 13 31 F = 3 a b 31 1 ( m o d 3 ) . . S i n c e r i g h t s i d e i s i n t e g e r , F i s a f a c t o r o f 2015. A l s o , t h e r i g h t s i d e m u s t b e a f a c t o r o f 3 : . I f F 1 ( m o d 3 ) [ m e a n i n g F = 13 o r 31 ] . ( 1 ) 2 2 1 1 1 2 ( m o d 3 ) F 13 o r 31 . I f F 2 ( m o d 3 ) [ m e a n i n g F = 5 ] . ( 2 ) 2 2 1 1 2 1 ( m o d 3 ) F = 5 { a }^{ 3 }+{ b }^{ 3 }=\quad (a+b)({ a }^{ 2 }-ab+{ b }^{ 2 })=(a+b)(\quad { (a+b) }^{ 2 }-3ab\quad )=5*13*31[factors\quad of\quad 2015]\\ \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad .\\ Let\quad (a+b)=F:\\ \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad .\\ F({ F }^{ 2 }-3ab)=5*13*31\\ \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad .\\ \quad ({ F }^{ 2 }-3ab)=\frac { 5*13*31 }{ F } \qquad \qquad \qquad \qquad \qquad \quad \quad 5\equiv 2(mod\quad 3)\\ \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \quad \quad \quad \quad \quad \quad 13\equiv 1(mod\quad 3)\\ { F }^{ 2 }-\frac { 5*13*31 }{ F } =-3ab\qquad \qquad \quad \quad \quad \quad \quad \qquad \nearrow \quad \quad 31\equiv 1(mod\quad 3)\\ \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad .\\ \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad .\\ \\ Since\quad right\quad side\quad is\quad integer,\quad F\quad is\quad a\quad factor\quad of\quad 2015.\quad Also,\quad \\ the\quad right\quad side\quad must\quad be\quad a\quad factor\quad of\quad 3:\\ \\ \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad .\\ \\ If\quad F\equiv 1(mod\quad 3)\quad \quad \quad \quad \quad \quad [meaning\quad F=13\quad or\quad 31]\\ \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad .\\ { (1) }^{ 2 }-\frac { 2*1*1 }{ 1 } \equiv 2(mod\quad 3)\quad \quad \quad \quad \quad \therefore F\neq 13\quad or\quad 31\\ \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad .\\ \\ If\quad F\equiv 2(mod\quad 3)\quad \quad \quad \quad \quad \quad [meaning\quad F=5]\\ \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad \qquad .\\ { (2) }^{ 2 }-\frac { 2*1*1 }{ 2 } \equiv 1(mod\quad 3)\quad \quad \quad \quad \quad \therefore \quad F=5\\ \\

We can easily notice that ( a + b ) 3 = a 3 + 3 a 2 b + 3 a b 2 + b 3 (a+b)^3 = a^3 + 3a^2b + 3ab^2 + b^3 . The expression can be simplified as following:

( a + b ) 3 = a 3 + b 3 + 3 a b ( a + b ) (a+b)^3 = a^3 + b^3 + 3ab\cdot (a+b)

a 3 + b 3 = ( a + b ) [ ( a + b ) 2 3 a b ] a^3 + b^3 = (a+b)\cdot [ (a+b)^2 -3ab]

We shall denominate S = a + b S = a+b (as S stands for sum ) and P = a b P=ab (as P stands for product ). Therefore:

2015 = S ( S 2 3 P ) 2015 = S\cdot (S^2-3P)

Also, let x = S x=S and y = S 2 3 P y=S^2-3P , so 2015 = x y 2015 = x\cdot y . By factoring the number 2015, we know that 2015 = 5 13 31 2015 = 5 \cdot 13 \cdot 31 . This leaves us with a total of 16 possibilities for the ordenate pair ( x , y ) (x,y) : ( 1 , 2015 ) , ( 2015 , 1 ) , ( 1 , 2015 ) , ( 2015 , 1 ) , ( 5 , 403 ) , ( 403 , 5 ) , ( 5 , 403 ) , ( 403 , 5 ) , ( 13 , 155 ) , ( 155 , 13 ) , ( 13 , 155 ) , ( 155 , 13 ) , ( 65 , 31 ) , ( 31 , 65 ) , ( 65 , 31 ) (1,2015),(2015,1),(-1,-2015),(-2015,1),(5,403),(403,5),(-5,-403),(-403,-5),(13,155),(155,13),(-13,-155),(-155,-13),(65,31),(31,65),(-65,-31) and finally ( 31 , 65 ) (-31,-65) . That's a lot of possibilities! We should make some further considerations in order to eliminate some of them, starting with all negative ones. As a a and b b are both integers, one could think x = 5 x= -5 and y = 403 y= -403 (for example) would be a valid solution; but we can perform a fast analysis that guarantees that S > 0 S > 0 (or x > 0 x>0 ), as follows:

Assuming a + b 0 a+b \leq 0 , then a b a \leq -b . So a 3 b 3 a^3 \leq -b^3 and a 3 + b 3 0 a^3 + b^3 \leq 0 , which is absurd. That means a + b > 0 a+b > 0 and, consequently, both x x and y y must be positive integers.

If a a and b b are the solutions of an equation, then it is the following:

z 2 S z + P = 0 z^2 -Sz + P = 0

As both solutions are integers (and therefore real numbers), S S and P P must satisfy S 2 4 P 0 S^2 - 4P \geq 0 . In terms of x x and y y , this means y 1 4 x 2 y \geq \frac {1}{4}x^2 . In the end, considering the possibilities which satisfy this condition and simultaneously guarantee that both S S and P P are integers, the only ordenate pair that "passes the test" is ( x , y ) = ( 5 , 403 ) (x,y) = (5,403) (meaning S = 5 , P = 126 S=5, P=-126 and a , b ) = ( 14 , 9 ) a,b) = (14,-9) or vice-versa).

We've developed the solution in order that our answer is x x (or S S ), so, therefore:

a + b = 5 a+b = 5

Hope it helped!

Amed Lolo
Feb 8, 2016

(a+b)^3=a^3+b^3+3ab^2+3ba^2. =2015+3ab(a+b) so. (a+b).((a+b)^2-3ab)=2015=5×403 a+b=5 or 403 .assume a+b=403. So ((a+b)^2-3ab=5 .so. (403)^2-3ab=5 so ab=(162409-5)\3=54134.67). which it is not an integer number &from given. a&b integer so ab must be integer number so a+b=5#########

403 is not prime (13•31). #Amed Lolo

Aryan Baghel - 5 years ago
Kumar Rb
Sep 23, 2015

a^3 + b^3 = 2015 means that: (a + b)(a^2 - ab + b^2) = 2015, where both (a + b) and (a^2 - ab +b^2) are integers.

The only pairs of integer factors of 2015 are: 1 and 2015 5 and 403 13 and 155 31 and 65,

and their negatives. For each pair, let (a + b) equal one factor, and let (a^2 - ab + b^2) equal the other factor. This gives a nonlinear system of equations that can be solved for a and b. Solving the system for each choice of (a + b) shows that the only choice that gives integer solutions for a and b is...a + b =5.

Les Schumer
Feb 11, 2021

The sum of cubes a 3 + b 3 a^3+b^3 can be written as ( a + b ) ( a 2 a b + b 2 ) (a+b)(a^2-ab+b^2)\\ Due to the symmetry of the expression, we can consider the factor pairs of 2015: { ( 1 , 2015 ) , ( 5 , 403 ) , ( 13 , 155 ) ( 31 , 65 ) } \\\{(1,2015),(5,403),(13,155)(31,65)\} and, as ( a + b ) < ( a 2 2 a b + b 2 ) ( a + b ) { 1 , 5 , 13 , 31 } (a+b) < (a^2-2ab+b^2) \rightarrow (a+b) \in \{1,5,13,31\}\\ Try ( a + b ) = 5 (a+b)=5\\ Then ( a 2 + 2 a b + b 2 ) = 25 (a^2+2ab+b^2)=25\\ Substracting ( a 2 a b + b 2 ) = 403 (a^2-ab+b^2)=403\\ Gives 3 a b = 378 a b = 126 3ab=-378 \rightarrow ab=-126 \\ The factor pairs of 126 are { ( 1 , 126 ) , ( 2 , 63 ) , ( 3 , 42 ) , ( 6 , 21 ) , ( 9 , 14 ) } \{(1,126),(2,63),(3,42),(6,21),(9,14)\}\\ Given the assumption that ( a + b ) = 5 (a+b)=5 we see that a = 14 a=14 and b = 9 b=-9 satisfies the balance of the equation hence ( a + b ) = 5 (a+b)=\boxed{5}

Hadia Qadir
Sep 2, 2015

a^3 + b^3 = 2015 means that: (a + b)(a^2 - ab + b^2) = 2015, where both (a + b) and (a^2 - ab +b^2) are integers.

The only pairs of integer factors of 2015 are: 1 and 2015 5 and 403 13 and 155 31 and 65

For each pair, let (a + b) equal one factor, and let (a^2 - ab + b^2) equal the other factor. This gives a nonlinear system of equations that can be solved for a and b. Solving the system for each choice of (a + b) shows that the only choice that gives integer solutions for a and b is...a + b =5.

Mehdi Balti
Sep 2, 2015

a^3 + b^3 = 2015 means that: (a + b)(a^2 - ab + b^2) = 2015, where both (a + b) and (a^2 - ab +b^2) are integers.

The only pairs of integer factors of 2015 are: 1 and 2015 5 and 403 13 and 155 31 and 65

For each pair, let (a + b) equal one factor, and let (a^2 - ab + b^2) equal the other factor. This gives a nonlinear system of equations that can be solved for a and b. Solving the system for each choice of (a + b) shows that the only choice that gives integer solutions for a and b is...a + b =5.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...